First records of Brachycrotaphus tryxalicerus (Fischer, 1854) in the Italian Peninsula (Orthoptera: Acrididae) - Viglioglia, Valerio; Carpaneto, Giuseppe Maria; Massa, Bruno (Fragmenta entomologica, 2020)
The authors report the first data of an Afrotropical and Mediterranean grasshopper, Brachycrotaphus tryxalicerus, for the Italian peninsula. In the Mediterranean area this species had been previously found only in Spain, Sicily and Egypt. A basic habitat description with details on the dominant vegetation is given for each locality of the Italian peninsula. Both these sites are subject to hot dry summers and rainy winters. Further investigations should be carried out in other Italian regions and in the Maghreb to search this species where it was never observed.